Components of litterfall production in a tropical deciduous forest of Northwest Mexico - Ana M Velez-Ruiz; Enrico A Yépez (PANGAEA, 2019)
This dataset contains information about the production and composition of litterfall at a successional gradient of the tropical deciduous forest of northwestern Mexico In these sites, the production was collected every fifteen days during the period from June 2018 to February 2019. We used sixty 0.5 m diameter litter traps (20 per site) made of synthetic mesh suspended at 75 cm from the ground. Contents from each bag were separated in leaves, branches, seeds, fruits, flowers and bark. Subsequently they were introduced in a drying oven for 48 hours at 65 °C. To calculate the amount of litter per unit area, the litter weight of each sample was divided by the area of the trap (0.19 m2), expressing the values in grams of litter per square meter (g m2). The sites are part of the private reserve "Monte Mojino" managed by Naturaleza y Cultura International. This reserve is whitin the "Area de Protección de Flora y Fauna Sierra de Alamos-Rio Cuchujaqui in Northwestern Sonora, México". At this reserve we work at three contiguous sites i) an old gowth forest, ii) a secondary forest (clear cut but in regeneration for over 35 years) and iii) early secondary succession forest patch with about 9 years of natural regeneration.
Supplement to: Velez-Ruiz, AM; Yépez, EA (2019): Componentes de la producción de hojarasca en un Bosque Tropical Seco del Noroeste de México. In: Paz-Pellat, F; Velázquez-Rodríguez. A & Rojo-Martinez M (eds) Estado Actual del Conocimiento del Ciclo del Carbono y sus Interacciones en México: Síntesis a 2019. Serie Síntesis Nacionales. Programa Mexicano del Carbono. Texcoco, Estado de México, México